Some New Results for Jaggi-<semantics>W</semantics>-Contraction-Type Mappings on b-Metric-like Spaces - Slobodanka Mitrović; Vahid Parvaneh; Manuel De La Sen; Jelena Vujaković; Stojan Radenović (Mathematics, 2021)
In this article, we generalize, improve, unify and enrich some results for Jaggi-<semantics>W</semantics>-contraction-type mappings in the framework of b-metric-like spaces. Our results supplement numerous methods in the existing literature, and we created new approach to prove that a Picard sequence is Cauchy in a b-metric-like space. Among other things, we prove Wardowski’s theorem, but now by using only the property (<semantics>W</semantics>1). Our proofs in this article are much shorter than ones in recently published papers.